Publication trends of research on conjunctival melanoma during 1997–2022: A 25-year bibliometric study - Xu, Wei; Yang, Ludi; Ge, Shengfang; Jia, Shichong; Gu, Fen (Frontiers in Oncology, 2022)
Background: Conjunctival melanoma (CM) is a life-threatening ocular tumor with a high rate of local recurrence and metastasis. Our objective is to analyze research trends in CM field and compare contributions from different countries, institutions and authors. Methods: We extracted all CM-related publications published from 1997 to 2022 from the Web of Science database and applied Microsoft Excel and VOSviewer to review publication data, analyze publication trends, and visualize relevant data. Results: A total of 708 publications were identified. The United States contributed the most publications (280) and citations (8,781 times) with the highest H-index value (47). The Ophthalmic Plastic and Reconstructive Surgery, British Journal of Ophthalmology, American Journal of Ophthalmology and Cornea were the most productive journal concerning CM, and Shields CL, Shields JA, Jager MJ as well as Finger PT had published the most papers in the field. Keywords were classified into three clusters: clinical research, management-related research and genetic research. The keywords "primary acquired melanosis", "metastasis" and "BRAF mutations" were most frequently emerged. According to the average appearing year (AAY), targeted therapy (AAY of 2019.0) and nivolumab (AAY of 2018.7) were identified as the main focuses of the field in the near future. Conclusion：In the past 25 years, the United States, Germany, England and the Netherlands held the leading position in the CM research. A group of scholars made important contributions to CM research and will continue to guide cutting-edge research. Treatments that have been shown to be effective for advanced cutaneous melanoma, such as targeted therapy and immunotherapy, are potential focuses for future CM research.